Bez slávy i bez diskuse, aneb ordinace žen v českých církvích - Nešpor, Zdeněk R. (Lidé města, 2020)
Ordination of women as ministers is an important issue of gender equality and social stratification. The liberally-oriented non-Catholic Czech churches introduced the ordination of females rather early – the Czechoslovak Hussite Church in 1947, and the Protestant Church of the Czech Brethren in 1953. In both cases, however, these were quite problematic steps, and female members of the clergy were long handicapped in comparison to their male colleagues, which the author attributes to the way this fundamental change was introduced in the churches. In the case of the Czechoslovak Hussite Church, this was a pragmatically motivated directive coming from “above”, which was not preceded by any discussion or education whatsoever. In the case of the Protestant Church, this was the assertion of a progressive theological orientation, the protagonists of which had been striving for this change for more than twenty years, however, again without adequate public discussion throughout the church. Both approaches thus caused negative consequences in the long-term. When considering the problematic acceptance of feminist theology and taking into account that when it came to ordaining women, both churches were de facto surpassed by two other – albeit socially less significant – religious groups in the Czech environment, one cannot be completely surprised by the fact that the anniversary of female ordination is not often commemorated, nor celebrated – and if so, then rather due to ignorance.